Career Networking as a Praxeological Communicative Practice of the XXI Century in Social Theory - Zoska, Yana V.; Scherbyna, Viktor M.; Kuzmin, Viktor V.; Stadnik, Oksana F.; Bondarenko, Olha V. (International Journal of Criminology and Sociology, 2021)
Career networking as a praxeological communicative practice is little studied in terms of effectiveness. The lack of research into the emotional, motivational, psychological and career effects of networking necessitates a study of the relationship between the types of career networking and these effects. The effects of networking in achieving career success were identified based on the electronic confidential survey of 102 employees of Ukrainian companies. The results of assessing the relationship between career networking types and emotional, motivational, psychological and occupational effects indicate that the relationship between variables is medium, low or absent. Therefore, the career effect is not related to networking, according to employees, if there is an average level of connection between the emotional, motivational, psychological effects and different types of networking. The study proves the subjectivity of the assessment of career networking and its effects. The article reveals the perception of career development methods: networking is perceived negatively as a way to achieve professional goals, which underestimates career performance. At the same time networking is perceived positively as a way to maintain friendship, motivation and level of satisfaction. The article confirms the connection between the subjective assessment of networking and the perception of networking as a "dirty and dishonest" way to get a job, achieve professional goals or career growth. In general, the subjective assessment of career networking causes low professional effects, while the emotional, motivational, psychological effects may be overestimated due to the positive perception of such effects by respondents.